Earth: The Odd Planet - Liu, Lin-Gun (European Journal of Applied Sciences, 2024)
As far as the atmospheric compositions are concerned, the Earth’s atmosphere is the only abnormality* in our Solar System. There is no compelling reason that, during and right after accretion, the Earth’s proto-atmosphere should be any different from those of Venus and Mars and the latter two probably maintain their proto-atmospheres until now. Apart from the different atmospheric composition, the Earth also possesses the oceans, the largest satellite (relative to its planet’s mass), and the greatest average density (5.52 g/cm3). The single big event of the giant Moon-making impact process in the early history can account for all these oddities of the Earth. The Moon-forming giant impact gave Earth the largest satellite (Moon) and released most of the Earth’s volatiles into its CO2-dominated proto-atmosphere. Most, if not all, H2O dissolved in the entrapped magma ocean escaped into the CO2-rich proto-atmosphere and reacted to form a supercritical H2O-CO2 mixture at relatively high pressure and high temperature. After solidification, the Earth’s surface temperature cooled down to about 450 300°C and the “dense” supercritical H2O-CO2 mixture precipitated to form the indigenous hot and soda oceans. The formation of the Earth’s oceans would somewhat remove CO2 from the proto-atmosphere. The removal was later accelerated and completed when the indigenous oceans reacted with plagioclase, the most abundant mineral on the Earth, to form carbonate and clay minerals. During the giant impact, whilst the rocky debris formed the Moon, the impactor’s iron core was incorporated in the Earth, which might account for the Earth’s highest mean density among all planets in our Solar System. The abnormality of the Earth implies its uniqueness which, in turn, may disappoint many scientists who are interested in searching for life on other planets. This is because the CO2-dominated proto-atmosphere cannot be removed due to the absence of oceans which requires a fair amount of supercritical H2O at high temperature and relatively higher atmospheric pressures.